Employee perspectives on safety citizenship behaviors and safety violations. (March 2017) - Chmiel, Nik; Laurent, Julie; Hansez, Isabelle
Highlights: Safety Citizenship Role Definitions (SCRDs) are associated with situational safety violations. Situational safety violations are those provoked by the Organization. Job control is related to SCRDs through perceived management commitment to safety. Job control is related to SCRDs through work engagement. Safety participation mediates the relationship between SCRDs and situational violations. Abstract: Two studies investigate whether employees viewing discretionary safety activities as part of their job role (termed safety citizenship role definitions, SCRDs) plays an important part in predicting two types of safety violation: routine violations conceptualized as related to an individual's available cognitive energy or 'effort'; and situational violations, which are those provoked by the organization (Reason, 1990). Study 1 showed SCRDs predicted situational violations only, and partially mediated the relationships between Perceived Management Commitment to Safety (PMCS) and work engagement with situational violations. These findings add to those by Hansez and Chmiel (2010), showing that routine and situational violations have predictors that differ. Study 1 findings also extend research reported by Turner et al. (2005), by showing that the effect of Job Control on SCRDs was mediated by both PMCS and work engagement. In study 2, participation in discretionary safety activities (safety participation) mediated the relationship between SCRDs and situational violations. Similar to study 1 The link between SCRDs and routine violations was non-significant and, strikingly, so was the link between safety participation and routine violations. These results support the view that processes involving SCRDs and safety participation are not cognitive-energetical in nature. In addition, study 2 findings extend previous work by Neal and Griffin (2006) by showing that SCRDs and safety knowledge partially mediated relationships between safety motivation and safety participation, whereas the direct effect of safety motivation on safety participation was non-significant. The results from both studies support the view that SCRDs are important in predicting situational violations. In study 2 SCRDs were shown to partially mediate the relationship between safety motivation and self-reported participation in discretionary safety activities (Safety Participation) which, in turn, related to situational violations. Interestingly there was no significant direct link between SCRDs and situational violations. These findings support the view that the effect of SCRDs on situational violations is fully mediated by participation in discretionary safety activities.